Psychometric properties of knee proprioception tests targeting healthy individuals and those with anterior cruciate ligament injury managed with or without reconstruction: a systematic review protocol. Issue 4 (4th April 2019) - Arumugam, Ashokan; Strong, Andrew; Tengman, Eva; Röijezon, Ulrik; Häger, Charlotte K
Abstract : Introduction: An anterior cruciate ligament (ACL) injury affects knee proprioception and sensorimotor control and might contribute to an increased risk of a second ACL injury and secondary knee osteoarthritis. Therefore, there is a growing need for valid, reliable and responsive knee proprioception tests. No previous study has comprehensively reviewed all the relevant psychometric properties (PMPs) of these tests together. The aim of this review protocol is to narrate the steps involved in synthesising the evidence for the PMPs of specific knee proprioception tests among individuals with an ACL injury and knee-healthy controls. Methods and analysis: The Preferred Reporting Items for Systematic reviews and Meta-Analyses will be followed to report the review. A combination of four conceptual groups of terms—(1) construct (knee proprioception), (2) target population (healthy individuals and those with an ACL injury managed conservatively or with a surgical reconstruction), (3) measurement instrument (specific knee proprioception tests) and (4) PMPs (reliability, validity and responsiveness)—will be used for electronic databases search. PubMed, AMED, CINAHL, SPORTDiscus, Web of Science, Scopus, the Cochrane Central Register of Controlled Trials and ProQuest will be searched from their inception to November 2018. Two reviewers will independently screen titles, abstracts and full text articles, extract data and perform risk of bias assessment using the updated COnsensus-based Standards for the selection of health Measurement INstruments risk of bias checklist for the eligible studies. A narrative synthesis of the findings and a meta-analysis will be attempted as appropriate. Each PMP of knee proprioception tests will be classified as 'sufficient', 'indeterminate' or 'insufficient'. The overall level of evidence will be ascertained using an established set of criteria. Ethics and dissemination: Ethical approval or patient consent is not required for a systematic review. The review findings will be submitted as a series of manuscripts for peer-review and publication in scientific journals. PROSPERO registration number: CRD42018108014.